ВПЛИВ РЕЖИМНИХ І ЕКСПЛУАТАЦІЙНИХ ФАКТОРІВ НА ДЕМПФЕРНУ СИСТЕМУ РОТОРА ЯВНОПОЛЮСНОЇ СИНХРОННОЇ МАШИНИ - Васьковський, Ю.М.; Гераскін, О.А. (Інститут електродинаміки НАН України, Київ, 2021)
The physical processes in the damping system of the salient-pole synchronous machine rotor, which cause the gradual destruction of its structure, have been studied. In particular, the distributions of currents, temperatures and thermomechanical stresses in the damping system rods during its operation in asynchronous and asymmetric modes of operation, as well as in case of rotor eccentricity. A field mathematical model has been developed that takes into account the combined action of three physical fields of different nature: electromagnetic, temperaturic, and thermomechanical stress fields, and allows estimating heating and thermomechanical loads in the damping system of the rotor of the salient-pole synchronous machine. According to the results of the analysis, the heating and thermomechanical loads of the structural elements were determined and recommendations for its structural improvement were given. References 9, figures 9, tables 1.